Mediating role of poverty in the association between environmental factors and cognitive performance in preschoolers - Fracchia, Carolina Soledad; Hermida, María Julia (Universidad Nacional de Córdoba. Facultad de Psicología, 2020)
The association between environmental factors and cognitive performance during childhood could be mediated by poverty (i.e., households with Unsatisfied or Satisfied Basic Needs). This study explored such mediating roles in preschoolers from different socioeconomic backgrounds. Tasks to assess executive attention, working memory, inhibitory control, planning, and fluid reasoning were administered to 250 children aged 4 and 5 years. The results suggested that poverty mediated the effects of family composition, child health, health risk factors, children and adults at home, maternal age, and literacy activities on the performance of executive attention, fluid reasoning, and inhibitory control. These results contribute to our understanding of the relationship between environmental factors and cognitive development through the identification of the mediating role of poverty.

La asociación entre los factores ambientales y el desempeño cognitivo durante la infancia podría estar mediada por la pertenencia a hogares pobres (i.e., hogares con necesidades básicas insatisfechas o satisfechas). Este estudio exploró tal mediación en preescolares de diferentes contextos socioeconómicos. Para tal fin, se administraron tareas que demandaron atención ejecutiva, memoria de trabajo, control inhibitorio, planificación y razonamiento fluido a 250 niños/as de 4 y 5 años. Los resultados sugirieron que la pobreza medió los efectos de la composición familiar, la salud infantil, los factores de riesgo para la salud, cantidad de niños/as y adultos en el hogar, la edad materna y las actividades de alfabetización sobre la atención ejecutiva, el razonamiento fluido y el control inhibitorio. Estos resultados contribuyen a la comprensión de la relación entre los factores ambientales y el desarrollo cognitivo a través de la identificación de la pobreza como variable mediadora
El rol mediador de la pobreza en la asociación entre factores ambientales y el desempeño cognitivo de preescolares
Keywords: Ciencias sociales::Ciencias de la educación